Customers' perceptions of factors influencing purchasing behavior of discounted price: Based on digital devices in case of Iran - Zomorrodian, Mohammad Ehsan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Recently, digital devices and electronic markets have become popular in many countries especially in Iran. These markets contribute to the national economy and significantly influence the financial power of the country. Companies are interested to achieve more competitive advantages by improving their service quality and providing their products with guarantee/warranty cards. Researchers found that, the success of buying/selling digital devices in this competitive market stems from both quality of the device and ability to provide products that meet customer’s needs and wants as well as the strategy of applying low prices. This thesis empirically investigates on factors which influence customers` behavior. First of all I assume that, there is no significant difference among of different gender groups in terms of their perceptions influencing purchasing behavior of discounted price. Secondly, there is no significant difference among of customers with different age groups in terms of their perceptions influencing purchasing behavior of discounted price. Thirdly, there is no significant difference among of customers with different income level groups in terms of their perceptions influencing purchasing behavior of discounted prices. The results of T-test and one-way Anova techniques show that, there are significant differences among customers with different gender, age and income level in terms of their perceptions to influence purchasing behaviour of discounted price. Keywords: Pricing strategy, Discount strategy, Customer behavior, and t-test and Anova analysis.

ÖZ: Digital ve elektronik piyasalar son yıllarda anlamlı bir büyüme sağlamışlardır. Dolayısı ile satış politikalarında servis kalitesi ve garanti sistemi çok önem kazanmıştır. Digital satışlarda esnek olabilme ve ucuz fiyata satabilme adına müşteri istekleri ve ihtiyaçları göz önünde tutulmaya başlanmıştır. Bu tez indirim faktörlerini kullanarak müşteri davranışlarının digital aletler üzerindeki etkilerini Iran’daki yerel piyasayı baz alarak ampirik olarak inceler. Bu çalışma üç ana noktada ele alınmıştır; müşterinin yüksek fiyata olan motivasyonu, iskontonun etkisi, ve iskonto stratejesi. T-değerleri ile Anova sonuçları gösteriyorki indirim faktörü müşterinin davranışları ve algılaması üzerinde çok büyük etkisi vardır. Indirim faktörü müşterileri olumlu yönde etkilemiştir. Sonuç olarak İran halkı miktar indiriminden ziyade fiyat indirime daha fazla eğilim göstermiştir. Anahtar kelimeler: İndirim stratejisi, fiyat stratejisi, İran piyasası, t-testi, Anova analizi, müşteri davranışları.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2014. Supervisor: Prof. Dr. Sami Fethi.
Keywords: Business Administration; Marketing Management; Marketing; Sales promotion; Pricing Strategy; Discount Strategy; Customer Behavior; t-test and Anova analysis